From Lists to Images: Exploring the Concept of the Good Teacher in Teacher Education - Grant, Kimberley A. (Journal of the Canadian Association for Curriculum Studies, 2015)
The question of what it means to be a good teacher is often addressed through lists of teacher traits, competencies, skills, beliefs, and practices. However, list-making runs the risk of fragmenting the complex, relational act of teaching and limiting the types of conversations that occur in teacher education. There is a small body of literature that attempts to explore this question through the use of images rather than lists. The aim of this paper is to foreground that research and the types of conversations it enables in order to begin to interrogate the images and corresponding discourses about good teachers that are held both individually and collectively.